Cyber Security of Robots: Integrating Safety and Security in Cognitive Social Computers - Parthiban, K; Kanchana, R; Sridhar, P S V S; Krishnamoorthy, N. V.; Aruna Sri, P.S.G. (Malikussaleh University, Aceh, Indonesia, 2025)
For social robots to coexist with people, they must be trustworthy and safe. This study examines the implications and relationships between cybersecurity and safety to develop more intelligent, secure, dependable autonomous robots. The initial findings are presented in this publication. Robots are used extensively in the modern world, not just in automated cars and medicine but also in industry, national security, and defence. Cyberattacks against robots and other security concerns are rising with the number of robots. We propose creating a robotic intrusion prevention system (RIPS) that employs a cutting-edge methodology to identify and stop intrusions in cyber-physical systems, including cognitive social robot systems. To mitigate cyber-physical risks, the RIPS uses system modes to specify which robotic system components limit or decrease its functioning when the system is penetrated. The RIPS detects threats at the robotic communication level. Additionally, we show that enhancements in encryption, authorisation/authentication, and physical security can considerably lower the probability of cybersecurity threats on robotic platforms. A dual regulatory framework that governs cybersecurity and physical product safety separately makes it challenging to regulate cyber-physical systems like care robots consistently and effectively. We conceive and talk about the difficulties in controlling the security of cyber-physical systems using the current dual framework, especially the absence of required certificates. Various robotic systems' security levels are examined in multiple domains to ascertain whether they need an upgrade or correction. Additionally, we outline and highlight open challenges that may emerge over the coming years.